Perkembangan Bahasa dan Sastra Arab di India - Al Jufri, Moh. Iza; Fitriani, Laily (Diwan: Jurnal Bahasa dan Sastra Arab, 2023)
The goals of this research are to 1) understand the development of Arabic language and literature in India; 2) understand the characteristics of Arabic literature in India; and 3) understand Arabic literature in India. The qualitative-descriptive method was used. This research data was obtained through the analysis of literature studies. Primary data sources include Ahmad Idris’s book Al Adab Al Arabi fi Syibh Al Qarrah Al Hindiyah, and secondary data sources include journals, books, theses, and other relevant scientific works. Reading, studying, and recording key points from primary and secondary sources about the development of Arabic language and literature in India is used to collect data. There are three types of data analysis techniques: data reduction, data exposure, and inferring research-related data. The findings of this study show that the Arabic language and literature evolved gradually in India over time, particularly during the Islamic dynasties of India. Its development is excellent and significant, particularly in the fields of education, scholars, literati, and literary works. Some general characteristics of Arabic literature in India include religious elements, praises, and laments; a mix of Persian and Indian literary elements; and so on. Famous writers include Abu ’Ata’ Al Sindhi, Abu Al ’Ula Al Lahori, Abdul Hayi Al Laknawi, and cleric Anwar Shah Al Kashmiri. مستخلص أهداف هذا البحث هي 1). معرفة تطور اللغة العربية وآدابها في الهندي، 2) معرفة خصائص الأدب العربي في الهند،3) معرفة الأدباء العربية في الهند. والمنهج المستخدم هو المنهج الوصفي. ومصدر البيانات الأولية هو كتاب الأدب العربي في شبه القارة الهندية لأحمد إدريس، والمصادر الثانوية هي المجلات العلمية والكتب الأدبية والأطروحات ذات صلة بموضوع البحث. وجمع البيانات من خلال قراءة ودراسة وملاحظة النقاط المهمة من المصادر الأولية والثانوية حول تطور اللغة العربية وآدابها في الهند. هناك ثلاث تقنيات لتحليل البيانات، وهي تلخيص البيانات وعرض البيانات واستنتاج البيانات المتعلقة بالبحث. تكشف نتائج هذا البحث أن اللغة العربية وآدابها قد تطورت في الهند تدريجيا بمرور الوقت، خاصة في ظل الأمارة الإسلامية في الهند، لاسيما في مجال التعليم والأعمال الأدبية. وخصائص الأدب العربي في الهند أنه يحتوي على عناصير دينية ومدح ورثاء وهناك مزيج من عناصر الأدب الفارسي والهندي. ومن أشهر الأدباء: أبو عطاء السندي، وأبو علاء اللاهوري، وعبد الحي اللكنوي، وأنوار شاه الكشميري. الكلمات المفتاحية: اللغة العربية وأدبها؛الهن